Estudo logístico para exportação do complexo soja - Corredor Ferroviário Centro Leste - Gonçalves, Inácio Marcelo (2011)
The railway modality is one of the most efficient ways to the outflow of agricultural products. Several agricultural producing regions face logistics problems, especially the region of the cerrado located in the middle of the country. This inefficiency causes additional costs to the agricultural products that are exported or to the ones consumed domestically. Therefore, the aim of this study was to identify the transport conditions of the soybean complex (grain, bran and oil) in the Central-East Railway Corridor, the most important exported agricultural product, in 2010, that ranked in the forth position of the exported Brazilian products, representing 8,50% (US$ 17.12 billion) in the trade balance. In this study was used the method of train capacity based on the Davies and Stevenson formulas to carry out an operational analyzes of the critical section during the transposition of the Serra do Tigre between the Km 694.880 and 782.552 of the EF 045 with a 3.08% ramp and minimum radius of curvature of 71,00 m which reduces severely the composing velocity and restrings the cargo capacity. The results showed that the trains can be a compound of 90 railway cars with maximum load of 7.600.00 tons. It was also estimated the cost of the railway transportation in this corridor between the Railway Station of Brejo Alegre (Araguari/MG) and the Railway Station Eldorado (Contagem/MG), considering fixed and variable costs. The achieved result was really close to the freight cost suggested by the National Agency of Land Transportation (ANTT).